Classroom Management, Collaboration and Teaching Strategies of a Teacher - Pandey, Shiv Ram; Kaudal, Durga Nidi; Pandey, Suprim (International Journal of Management, Innovation, and Education, 2025)
This research article is on ‘Classroom Management, Collaboration and Teaching Strategies of a Teacher’ for English Language Learning in a Private School in Kathmandu. This case study research explores how private school teacher creates classroom management and teaching strategies for collaborative learning environment for the English language learners. The study adopted qualitative research method and case study design to collect and analyze data from a single participant. In-depth interview and observation techniques were used to collect rich data. The participant was selected purposively. The study showed that without having teaching qualification, the teacher was recruited to teach English in the school. It raised a question that whether or not the concerned department of the government treats government and private schools equally. It also indicates that the stakeholders such as parents and community in the school perhaps were not much involved in educational activities of the school. It is expected that the research outcome provides a significant ground for creativity, innovation, research, rethinking and reforming in an area of classroom management, collaboration and teaching strategy in Nepal.